DISCRETE FUZZY FILTER OF UAV’S FLIGHT PARAMETERS - Bocharnikov, Victor P.; Bocharnikov, Ilya V. (Proceedings of National Aviation University (archive), 2010)
The robust discrete filter for flight information parameters estimation of Unman Arial Vehicle in conditions of nonstationary and not additive disturbance influence, with unknown parameters, is synthesized. The filter based on the theory of fuzzy measure and fuzzy-integral calculus. An estimation of the signal is determined by fuzzy images of the signal estimated value at the previous step of the measured signal and by selection of filtration function. The investigations of the efficiency of synthesized fuzzy filter are performed.